2021
DOI: 10.1111/1744-7917.12915
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of conspecifics from heterospecifics in a hybrid zone: Behavioral and chemical cues in ants

Abstract: Species and nestmate recognition in social insects occurs mostly through cuticular hydrocarbons acting as chemical cues. These compounds generate a colony-specific odor profile depending on genetic and environmental factors. Species and nestmate recognition results in specific behavioral responses, regulating the level of aggression toward other individuals during an interaction. Although species discrimination and recognition cues have been poorly studied in the context of interspecific hybridization, such sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…The latter case could be partly explained by the homogeneous environmental conditions within the studied area. InCordonnier et al (2022), higher levels of aggression were observed between allopatric individuals compared with individuals sharing similar environmental characteristics. Here, the relative similarity between nests in terms of substrate or available food could also have induced a homogenisation of cuticular hydrocarbons, with a consequent reduction in recognition of non-nestmates and aggressiveness(van Zweden & d'Ettorre, 2010).…”
mentioning
confidence: 96%
“…The latter case could be partly explained by the homogeneous environmental conditions within the studied area. InCordonnier et al (2022), higher levels of aggression were observed between allopatric individuals compared with individuals sharing similar environmental characteristics. Here, the relative similarity between nests in terms of substrate or available food could also have induced a homogenisation of cuticular hydrocarbons, with a consequent reduction in recognition of non-nestmates and aggressiveness(van Zweden & d'Ettorre, 2010).…”
mentioning
confidence: 96%